Wiedza z zakresu opieki żywieniowej i postrzegalna jakość tej opieki u pielęgniarek - Alagem Mizrahi, Aviva; Waszyńska, Katarzyna (Studia Edukacyjne, 2020)
Purpose: This study was conducted on nurses from The Sheba Medical Center. The purpose of the study was to investigate nurses’ evaluation of the importance of a nutrition assessment, (b) nurses’ knowledge of nutrition care and (c) nurses’ evaluation of the quality of nutrition care in their department. Design: The study was a quantitative correlational study performed in a university-affiliated, teaching hospital. Methods: Data were collected via a digital questionnaire through head nurses, from 203 nurses and analyzed by frequencies, means and Pearson correlations, independent t-tests, oneway ANOVA and stepwise such as the ability of patients to feed themselves, chew and swallow, multiple linear regression were performed to determine predictors observing whether a patient finishes a meal and offering assistance of nurses’ responses where needed. Findings: Importance of nutritional assessment is positively and significantly correlated to knowledge of nutritional care and quality of nutritional treatment. Female nurses’ knowledge is significantly higher than male. Senior nurses’ knowledge is higher than less senior nurses. Nurses who participated in emergency care training have a significantly higher level of knowledge than nurses who did not participate in this course. Knowledge of nutritional care is not significantly correlated to quality of nutritional treatment. It is important to introduce the role of nurses regarding nutritional care within their departments to doctors and dietitians, as well as involving them in building the intervention course. Conclusions: These findings highlight the importance of checking the quality of nurses’ educational knowledge and improving it through an intervention with specified training surrounding knowledge regarding nutrition, including learning and training.